Cloning and nucleotide sequence of the Bacillus subtilis ansR gene, which encodes a repressor of the ans operon coding for L-asparaginase and L-aspartase. - Sun, D (1993)
Previous work has shown that expression of the Bacillus subtilis ans operon which codes for L-asparaginase and L-aspartase, is both increased and made insensitive to repression by NH4+ by the aspH1 mutation. In current work, the gene in which the aspH1 mutation resides has been identified and sequenced; this gene, termed ansR, is immediately upstream of, but transcribed in the opposite direction from, the ans operon. The promoter region of ansR contains -10 and -35 sequences similar to those recognized by RNA polymerase containing the major vegetative-cell sigma factor sigma A, and ansR appears to be monocistronic. The ansR gene codes for a 116-residue protein, but the aspH1 mutant allele has an additional guanine residue at codon 55, resulting in generation of a truncated polypeptide of only 58 residues. Insertional inactivation of ansR resulted in a phenotype identical to that of the aspH1 mutant. The predicted amino acid sequence of the ansR gene product (AnsR) was homologous to that of the repressor of B. subtilis prophage PBSX, and a helix-turn-helix motif, characteristic of many DNA-binding proteins, was present in the AnsR amino-terminal region. These results suggest that ansR codes for a repressor of the ans operon.